Rationale for the ASSAIL-MI-trial: a randomised controlled trial designed to assess the effect of tocilizumab on myocardial salvage in patients with acute ST-elevation myocardial infarction (STEMI). Issue 2 (15th October 2019) - Anstensrud, Anne Kristine; Woxholt, Sindre; Sharma, Kapil; Broch, Kaspar; Bendz, Bjørn; Aakhus, Svend; Ueland, Thor; Amundsen, Brage H; Damås, Jan Kristian; Hopp, Einar; Kleveland, Ola; Stensæth, Knut Haakon; et al.
Abstract : Introduction: Interleukin-6 (IL-6) may be involved in ischaemia-reperfusion injury and myocardial remodelling after myocardial infarction (MI). We have recently shown that IL-6 inhibition by tocilizumab attenuates systemic inflammation and troponin T-release in patients with acute non-ST elevation MI (NSTEMI). Experimental studies suggest that IL-6 inhibition can limit infarct size through anti-inflammatory mechanisms, but this has not been tested in clinical studies. With the ASS essing the effect of A nti- IL -6 treatment in MI (ASSAIL-MI) trial, we aim to examine whether a single administration of the IL-6 receptor antagonist tocilizumab can increase myocardial salvage in patients with acute ST-elevation MI (STEMI). Methods and analysis: The ASSAIL-MI trial is a randomised, double blind, placebo-controlled trial, conducted at three high-volume percutaneous coronary intervention (PCI) centres in Norway. 200 patients with first-time STEMI presenting within 6 hours of the onset of chest pain will be randomised to receive tocilizumab or matching placebo prior to PCI. The patients are followed-up for 6 months. The primary endpoint is the myocardial salvage index measured by cardiac MRI (CMR) 3–7 days after the intervention. Secondary endpoints include final infarct size measured by CMR and plasma markers of myocardial necrosis. Efficacy and safety assessments during follow-up include blood sampling, echocardiography and CMR. Ethics and dissemination: Based on previous experience the study is considered feasible and safe. If tocilizumab increases myocardial salvage, further endpoint-driven multicentre trials may be initiated. The ASSAIL-MI trial has the potential to change clinical practice in patients with STEMI. Registration: Clinicaltrials.gov, identifier NCT03004703 .